Study on Thermoelectric Cooler Driven by Solar Energy in Medan City - Sitorus, Tulus Burhanuddin; Lubis, Zulkifli; Ariani, Farida; Sembiring, Ferry (Politeknik Elektronika Negeri Surabaya (PENS), 2018)
The primary purpose of this study is to investigate the performance of thermoelectric cooler driven by solar energy in Medan city, Indonesia. This cooler able to use in a remote area where electricity is still not available. The cooler could be used to store beverage that must be stored at low temperatures to maintain the freshness such as drink cup. The solar thermoelectric cooler is based on the principles of a thermoelectric module or Peltier effect to create a hot side and a cold side. The cold side of the thermoelectric module is utilized for cooling purposes to the cooling space. The heat from the hot side of the module is rejected to ambient surroundings by using heat sinks and fans. The solar thermoelectric cooler was experimentally tested for the cooling purpose. Experimental results showed that the solar thermoelectric cooler could reduce the temperature of the drink cup from 26oC to 15oC in approximately 40 min. The maximum COP of the cooling system during the experiment was calculated and found to be about 0.356. The effect of weather conditions on the COP value was about 85.90%.